PHASE 2 RANDOMIZED STUDY (ORION-1) OF A NOVEL, BIODEGRADABLE DEXAMETHASONE IMPLANT (AR-1105) FOR THE TREATMENT OF MACULAR EDEMA DUE TO CENTRAL OR BRANCH RETINAL VEIN OCCLUSION. Issue 1 (14th January 2023) - Singer, Michael A.; Boyer, David S.; Williams, Stuart; McKee, Hayley; Kerr, Kevin; Pegoraro, Tyler; Trevino, Leo; Kopczynski, Casey C.; Hollander, David A.
Abstract : Supplemental Digital Content is Available in the Text. AR-1105 is a novel biodegradable, sustained-release intravitreal dexamethasone implant formulated to provide 6-month durability. Two formulations of AR-1105 with different release profiles were well tolerated and demonstrated clinically meaningful and sustained improvements in vision and reduction in retinal thickening despite longstanding edema due to branch or central retinal vein occlusion. Abstract : Purpose: AR-1105 is a novel biodegradable sustained-release dexamethasone implant designed to deliver 6-month durability. This Phase 2 study evaluated two AR-1105 formulations with different release profiles in patients with macular edema due to retinal vein occlusion. Methods: Patients received a single intravitreal injection with 340 µ g dexamethasone. In the initial phase, five patients received clinical formulation (CF) 1. In the randomized phase, 44 patients were randomized 1:1 to CF1 or CF2. The follow-up was 6 months. Patients had vision loss due to macular edema diagnosed ≥9 (central retinal vein occlusion) or ≥12 months (branch retinal vein occlusion) before screening, and could be treatment-naive or -experienced (if received prior steroids, must have demonstrated response). Results: Both formulations improved vision and reduced retinal thickening from baseline across all visits. At Month 6, mean changes in best-corrected visual acuity were +4.3 and +8.0 letters, and mean changes in central subfield thickness were −93 µ m and −211 µ m in CF1 and CF2 randomized patients, respectively. Most common adverse events were reduced visual acuity, worsening macular edema, conjunctival hemorrhage, and increased intraocular pressure. No patients required surgery or laser for intraocular pressure control. Conclusion: Both formulations were well tolerated and demonstrated clinically meaningful and sustained improvements in vision and retinal thickening in patients with retinal vein occlusion with longstanding edema.